A novel symbiotic relationship between mites and recluse spiders (Sicariidae: Loxosceles), with a description of a new Callidosoma species (Trombidiformes: Erythraeidae) - Bernardi, Leopoldo Ferreira De Oliveira; Wohltmann, Andreas; Lorenzon, Isabela M; Ferreira, Rodrigo Lopes (Zootaxa, 2017)
This study reports a symbiotic association between an unknown species of Loxosceles (Araneae: Sicariidae) and the adults of a new species of parasitengone mite that lives on their web in Brazilian caves. This mite is described as Callidosoma cassiculophylla sp. nov. (Parasitengona: Erythraeidae). The symbiotic association is clearly beneficial for the mite, which lives with the spider, and feeds on prey captured by their webs, without any aggressive behavior or expulsion of the mites by the spiders.